PENYULUHAN PENCEGAHAN KEKERASAN TERHADAP PEREMPUAN DALAM RUMAH TANGGA DI BPPKB (BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA) KABUPATEN CIREBON (PELAKSANAAN DI DESA TUK KECAMATAN KEDAWUNG KABUPATEN CIREBON) - Hery Nariyah (Jurnal Ilmiah Publika, 2016)
ABSTRACT Violence against women today is an interesting matter because it is widely discussed by practitioners, non-governmental organizations (NGOs), academics and the wider community. This was motivated by the demands of a more complex role of women in line with the times that tend to pay more attention to Human Rights (HAM) without looking at or differentiating gender.Activities carried out by the author use qualitative methods with descriptive analysis studies because the writer wants to describe and explain an event or situation. As described by Rachmat (1994: 24), that descriptive research only describes situations or events, does not test hypotheses.Domestic violence (domestic violence) is a problem that often occurs in households. Therefore, prevention must be done early. Religious education and the practice of religious teachings in the household are the keys to success in preventing domestic violence.To prevent domestic violence in the household, love, and compassion must be developed early on. Mother can play a big role in teaching children at home to love and love each other. Because the main perpetrators of domestic violence are generally husbands, the role of religious leaders, educators, sociologists, and intellectuals must be at the forefront to continue to voice the importance of the household as the smallest unit in society to be built well and away from domestic violence. In order to communicate this to the wider community, the role and participation of the media are very important and decisive.Practice a saying "My house is my palace". However the situation is a house, the house must be a place that gives warmth, calmness, peace, protection, and happiness to all family members.